3-Dimensional mesothelioma spheroids provide closer to natural pathophysiological tumor microenvironment for drug response studies - Shi, Huaikai; Rath, Emma M.; Lin, Ruby C. Y.; Sarun, Kadir Harun; Clarke, Candice Julie; McCaughan, Brian C.; Ke, Helen; Linton, Anthony; Lee, Kenneth; Klebe, Sonja; Maitz, Joanneke; Song, Kedong; et al. (Frontiers in Oncology, 2022)
Traditional studies using cancer cell lines are often performed on a two-dimensional (2D) cell culture model with a low success rate of translating to Phase I or Phase II clinical studies. In comparison, with the advent of technologies, three-dimensional (3D) cell culture has been championed as the latest cellular model system that better mimics in vivo conditions and pathological conditions such as cancer. In comparison to biospecimens taken from in vivo tissue, the details of gene expression of 3D culture models are largely undefined, especially in mesothelioma – an aggressive cancer with very limited effective treatment options. In this study, we examined the veracity of the 3D mesothelioma cell culture model to study cell-to-cell interaction, gene expression and drug response from 3D cell culture, and compare them to 2D cell and tumour samples. We confirmed that 3D cells grown using the spheroid methods expressed highly interconnected cell-to-cell junction via SEM analysis. The 3D spheroids revealed to be an improved mini-tumour model as indicated by the TEM visualization of cell junctions and microvilli, features not seen in the 2D models. Growing 3D cell models using decellularized lung scaffold provided a platform for cell growth and infiltration for all cell types including primary cell line. Cells grown in spheroids using low-adhesive U-bottom plates were the most time-effective method. However, not every cell type grew into a 3D model using the hanging drop or poly-HEMA methods. Cells grown in 3D showed more resistance to chemotherapeutic drugs with reduced apoptosis. 3D cells stained with H&E showed cell-to-cell interaction and internal architecture that better represents that of in vivo patient tumours when compared to 2D cells. IHC staining revealed increased protein expression in 3D spheroids compared to 2D culture. Lastly, cells grown in 3D showed very different microRNA expression when compared to that of 2D counterparts. In conclusion, 3D cell models, regardless of which method is used showed a more realistic tumour microenvironment for architecture, gene expression and drug response, when compared to 2D cell models, and thus are superior preclinical cancer models.